Effectiveness of Oil Filling in Tight Sandstone Reservoirs of Yancheng Formation in Ordos Basin - Yu Han; Peiru Wanyan; Haoli Wang; Mengfei Qu; Hanlie Cheng; Fahim Theon (Journal of Chemistry)
The Ordos basin is one of the important oil-bearing basins in China, with abundant tight sandstone oil resources, wide distribution, and large thickness. It is the most realistic field of unconventional oil and gas exploration in China, and it is also an important oil and gas replacement resource at present. Oil accumulation in tight reservoirs is obviously different from conventional oil and gas accumulation, and the key lies in studying the effectiveness of oil filling in tight reservoirs. In order to solve this problem, this paper takes the tight sandstone reservoir of Member 7 of the Yancheng Formation in Ordos Basin as the research object, introduces the geological characteristics of this area after sorting out the previous research results, carries out the physical simulation experiment of oil filling, studies the relationship between the filling pressure and the lower limit of the filling throat, analyzes the effective accumulation space of the tight sandstone reservoir, defines the oil filling mechanism of the tight sandstone reservoir, and discusses the effectiveness and reservoir-forming effect of oil filling in different types of reservoirs. The results show that the rock types of tight sandstone reservoirs in the 7th member of the Yancheng Formation are mainly lithic feldspathic sandstone and feldspathic lithic sandstone, and the reservoirs have experienced strong compaction and carbonate cementation. The late iron-bearing carbonate cementation has further strengthened the degree of reservoir densification, and the reservoirs have been densified at the time of large-scale oil and gas filling. Through the simulation experiment of oil filling with natural cores with different physical properties, the relationship model between filling pressure and effective accumulation space of different types of tight sandstone reservoirs in Member 7 of the Yancheng Formation is established. With the change in filling pressure, the change trend and range of effective accumulation space of different types of tight sandstone reservoirs are obviously different. According to the relationship model between the filling pressure and the lower limit of the effective filling pore throat, the oil filling effectiveness of different types of tight sandstone reservoirs in the 7th member of the Yancheng Formation is determined. Class I and class II1 reservoirs are effective reservoirs for oil filling of tight sandstone reservoirs, which constitute the main oil-bearing section of tight sandstone reservoirs in member 7 of the Yancheng formation, while class II2 reservoirs are poor tight reservoirs, and class III reservoirs are basically oil-free, which are noneffective reservoirs for oil filling of tight sandstone reservoirs. The results provide theoretical data support for the next step of oil exploration and exploitation in tight sandstone reservoirs.